Acute compartment syndrome of the forearm associated with transradial coronary intervention. (October 2020) - Lee, Young-Keun; Lee, Se-Hwan; Kwon, Tae-Young
This study documents our experience with acute forearm compartment syndrome after percutaneous transradial coronary artery intervention and suggests several strategies to achieve good results. A retrospective review identified the medical records of four patients with acute forearm compartment syndrome after transradial intervention who were treated by urgent fasciotomy. The mean time from the onset of symptoms to operation was 5.7 hours. In three cases bleeding was from radial artery rupture at the puncture site, and one case was caused by brachial artery rupture at the level of the distal humerus and radial artery rupture at the level of proximal forearm. We obtained satisfactory results without any complications. If acute forearm compartment syndrome after transradial intervention is diagnosed, the site of bleeding should be identified preoperatively. Early surgical decompression produced satisfactory results even in elderly patients. Level of evidence: IV